Антикиллер: роман / Д. А. Корецкий - Корецкий Данил Аркадьевич (Вне закона, 1997)
Экземпляры: аб. (2010) / Инвентарный номер: 53231 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 66 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44